Together Means More Happiness: Relationship Status Moderates the Association between Brain Structure and Life Satisfaction. (1st August 2018) - Zhu, Xingxing; Wang, Kangcheng; Chen, Li; Cao, Aihua; Chen, Qunlin; Li, Junchao; Qiu, Jiang
Highlights: Life satisfaction was negatively related with cortical thickness of the left SFG and the bilateral MFG. The right MFG and left SFG thickness interacted with relationship status to predict self-report life satisfaction. Perceived stress lowered the moderation effect of relationship status, but not socioeconomic status and emotional support. Abstract: Life satisfaction reflects an individual's general evaluation of their overall quality of life. It has been hypothesized that relationship status (i.e. state of intimate relationship such as marriage, unmarried cohabiting, dating with others, single or divorce) may influence individual life satisfaction. However, there is little accessible empirical evidence that allows us to explore this proposition. Using a large sample of young adults ( n  = 1031) from the Human Connectome Project (HCP), we showed that compared to other relationship statuses (e.g., individuals who were single or divorced, individuals who dated others, and etcetera), marriage/cohabitation subjects not only revealed a higher life satisfaction plus higher emotional and instrumental support, but also reduced perceived stress, which contributed to higher life satisfaction. Using general linear model with cortical thickness as the dependent variable, life satisfaction was negatively associated with the left superior frontal gyrus (SFG) and bilateral middle frontal gyrus (MFG). Interestingly, both right MFG and left SFG could interact with relationship status to predict self-reported life satisfaction, in addition to being associated with a much lower life satisfaction in non-married/cohabiting individuals. These effects were independent of emotional, instrumental support, and socioeconomic status. Besides, statistical significance of the moderation effect pertaining to relationship status was lost once perceived stress was included as a covariate into the moderation model. Our findings provided empirical evidence for the potentially positive role of relationship status in life satisfaction, and also showed that remission of stress may be a critical factor.